Tracing the Underlying Operations, Processes, and Path Dependencies: The Microfoundations of Dynamic Capabilities in Educational Institutions - Daniel Ong Kim Kui; Rinto Rain Barry; Yohana F. Cahya Palupi Meilani (Journal of Economics and Management, 2026)
The strategy of education institutions to adapt and renew their resources and capabilities has become an increasingly critical issue, particularly with demographic shifts, intensifying competition, and resource constraints that threaten school operations. This study examines how microfoundations contribute to school sustainability and unpacks operational practices that enable organizational sustainability in educational institutions. Adopting a qualitative multiple-case study design, the study investigates eight secondary private schools in Indonesia with varying operational capabilities and performance. Data were collected through in-depth interviews, the school's operational plan, and activity observations, which were studied using thematic multi-case analysis. The findings reveal that schools' sustainability depends on how quickly they reorganize and build their strategic assets, such as processes, capabilities, technologies, and community feedback, to become new competitive advantages. Schools with stronger human resources, functional operational systems, and adaptive leadership were better able to sense shifts in the external environment, innovate in educational services, and reconfigure organizational practices. In contrast, schools experiencing failure showed weak individual-level actions and routines, despite having had strong positions in the past. The study proposes a strategic model that conceptualizes schools as capability-driven, grounded in microfoundations, to ensure a successful, result-oriented path. Theoretically, the findings confirm and extend the application of Dynamic Capability Theory in non-profit education contexts. In practice, the study offers strategic insights for school leaders, foundations, and policymakers seeking to enhance the sustainability of private secondary schools through various managerial routines.